ANALISIS KETERAMPILAN SOSIAL SISWA DALAM PEMBELAJARAN DARING DI KELAS V SDN 2 MEKARASIH - Citrasari, Neng Intan Nurhilma; Muslihah, Neni Nadiroti; Permana, Hendra (caXra: Jurnal Pendidikan Sekolah Dasar, 2021)
Based on the results of pre-observations, that the social skills of fifth grade students of SDN 2 Mekarasih in interacting, communicating, building teams / groups and solving problems are still low (lacking). This can affect student activity in the online learning process which is also a new challenge for teachers to be able to develop students' social skills. This study aims to determine the development of these four students 'social skills in online learning and to determine the contribution of online learning activities to the development of students' social skills. This research is a qualitative descriptive study with a naturalistic approach, using questionnaires and interviews as data collection tools. The results showed that the social skills of fifth grade students of SDN 2 Mekarasih in these four aspects were included in the strong category with a total score of 76.47%, as for the contribution of online learning activities, the results obtained were able to assist teachers in developing students' social skills by based on learning activities carried out in groups can develop these four aspects of social skills.